2016
DOI: 10.1186/s12906-016-1403-7
|View full text |Cite
|
Sign up to set email alerts
|

In vitro anti-HIV and antioxidant activity of Hoodia gordonii (Apocynaceae), a commercial plant product

Abstract: Background Hoodia gordonii products are widely commercialized for anti-obesity purposes; however, minimal research is available on the other health properties demonstrated by this popular herbal plant.Methods H. gordonii crude extracts (ethanol and ethyl acetate) were assayed for in vitro anti-HIV-1 protease (PR), reverse transcriptase (RT) and integrase activity. The 2,2-diphenyl-1-picrylhydrazyl (DPPH) and reducing power assays were used for the antioxidant analysis. In addition, qualitative and quantitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…The higher increase in both SOD and CAT in fish fed with UFME compared to fish fed with control diet indicated that UFME maintaining an adequate antioxidant status in the body. Similar findings were observed by Kapewangolo et al, (2016) and Akbary and Aminikhoei, (2018). The powerful anti-oxidative properties of UFME were additional proven by its efficiency to improve anti-oxidative abilities in blood, gills, liver and muscle of tilapia.…”
Section: Ta B L Esupporting
confidence: 90%
“…The higher increase in both SOD and CAT in fish fed with UFME compared to fish fed with control diet indicated that UFME maintaining an adequate antioxidant status in the body. Similar findings were observed by Kapewangolo et al, (2016) and Akbary and Aminikhoei, (2018). The powerful anti-oxidative properties of UFME were additional proven by its efficiency to improve anti-oxidative abilities in blood, gills, liver and muscle of tilapia.…”
Section: Ta B L Esupporting
confidence: 90%
“…In addition, both ethanol and ethyl acetate extracts had weak inhibition against HIV-1 integrase (IN) with <50% inhibition at the highest concentration tested of 400 μg/mL. Sodium azide was used as a positive control compound for IN inhibition [ 101 ]. In the same study, phytochemical screening of Hoodia gordonii was revealed the presence of phenolics, alkaloids, terpenes, steroids, cardiac glycosides and tannins in the ethanolic extract, while the ethyl acetate extract only showed the presence of phenolics, cardiac glycosides and steroids.…”
Section: Plant Extracts and Some Secondary Metabolites With Anti-hmentioning
confidence: 99%
“…Additionally, SOD is a crucial enzyme that eliminates ROS, which poses a hazard to cells under stress by inflicting spectacular damage to the cell structure and biomolecular function, promptly or incidentally leading to a variety of disorders (Costa et al, 2010). This research concludes that fish‐fed LP had greater SOD and CAT activity than fish fed the control and DCP diets, suggesting that phytase enzyme might modulate the Nile tilapia's antioxidant status (Kapewangolo et al, 2016). These findings corroborate those made by Adeshina, Akpoilih, Udom, et al (2023), who claimed that phytase enzyme (1000 FTU/kg) heightened catalase activity and superoxide dismutase activity.…”
Section: Discussionmentioning
confidence: 94%